Effect of brisk walking workplace programme on cardio respiratory fitness in young men with cardiovascular risks / Norsuhana Omar … [et al.] - Ahmad, Rozaziana; Mohd Shah, Mohd Shahrulsalam; Aminuddin, Amilia; Chellappan, Kalaivani; Omar, Norsuhana (Universiti Teknologi MARA, 2021)
Community-based health programmes at workplace involves planning, implementation and evaluation with the aim of empowering employees to gain control over their health. Brisk walking was a form of exercise that was acceptable to most people and may be integrated easily into daily routine. The aim of this study was to evaluate the improvement of cardio respiratory fitness (CRF) through a pedometer-based walking programme at the workplace. A total of 70 young men who were sedentary, achieving less than 5,000 steps/day in casual walking with 2 or more cardiovascular risk factors were recruited. Subjects were randomly assigned to a control (CG) (n=34; no change in walking) and pedometer group (PG) (n=36; minimum target: 8,000 steps/day). Blood lipid profile, anthropometric and CRF were measured at baseline and after 12 weeks. At post intervention, the PG increased step count and results for lipid and anthropometrics variables were significantly improved for time and group effect (p<0.001). In PG, the CRF was significantly increased for time and effect (p<0.01) for VO2peak from 31.54 ± 9.66 to 40.15± 9.55(ml/kg/min but no change in CG (31.46 ± 6.15 vs 31.60 ± 8.99 ml/kg/min). The walking programme improved health status in terms of improving biophysical profiles and cardiorespiratory fitness.